2015
DOI: 10.1007/s00381-015-2675-9
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in children with dysembryoplastic neuroepithelial tumors of the brain—A review of surgical outcomes across several studies

Abstract: PurposeIn children and adolescents, dysembryoplastic neuroepithelial tumors (DNETs) of the brain present with seizures almost 100 % of the time, potentially creating significant long-term morbidity and disability despite the generally indolent course of the lesion. These tumors also tend to be quite resistant to anti-epileptic drugs which, themselves, can be associated with long-term side effects and resultant disability. Many clinicians advocate early surgical resection of these lesions, but how effective thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 109 publications
2
30
0
1
Order By: Relevance
“…Medial temporal lobe is a site of predilection for DNET, mesial temporal sclerosis and herpes encephalitis which are known to be highly associated with epilepsy 15,16 . The great majority of these patients (15 of 18 patients) in the current study are shown to experience epilepsy/seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Medial temporal lobe is a site of predilection for DNET, mesial temporal sclerosis and herpes encephalitis which are known to be highly associated with epilepsy 15,16 . The great majority of these patients (15 of 18 patients) in the current study are shown to experience epilepsy/seizures.…”
Section: Discussionmentioning
confidence: 99%
“…7,40) Therefore, the etiology of tumor-induced seizures is multifactorial and extends beyond the physical size of the tumor itself. 41,42) Factors associated with seizure outcomes after epilepsy surgery for LEATs…”
Section: Epileptogenesis Of Leatsmentioning
confidence: 99%
“…Several studies that included large numbers of patients confirmed that gross total resection is among the strongest factors leading to seizure freedom after LEAT resection. 41,[56][57][58] However, some studies have stated otherwise. 49,50,59,60) Gross total resection may not be possible if the tumor is located adjacent to eloquent areas or other functional cortical areas.…”
Section: Degree Of Tumor Resectionmentioning
confidence: 99%
“…The most robust predictor of complete seizure freedom across available studies has been the extent of tumor resection (61,64 (65,66). The high rate of seizure freedom after surgery in patients with neoplasm-related epilepsy is especially meaningful given the long expected survival in children harboring low-grade brain tumors (67).…”
Section: Temporal Lesionectomymentioning
confidence: 99%